PENGARUH PENGGUNAAN CORN DRIED DISTILLERS GRAINS WITH SOLUBLES DALAM RANSUM TERHADAP PERFORMAN PUYUH JANTAN - Hestu Widyatmoko; Zuprizal (Zuprizal); Wihandoyo (Wihandoyo) (Buletin Peternakan, 2013)
Feeding trial were conducted to study the effect of the use of corn dried distillers grains with solubles (DDGS) in the diets on growth performance of male coturnix. One hundred and twenty male coturnixs were allotted into four dietary treatments containing 0, 10, 20 and 30% DDGS respectively in a Completely Randomized Design. Each treatment was replicated eight times. Feed and water were provided ad libitum. The variables observed were feed intake, average daily gain and feed conversion ratio. The data were analyzed using 0ne Way of analyses of variance (ANOVA). The result indicated that there was no effect of DDGS on the feed intake, average daily gain and feed conversion ratio. It could be concluded that DDGS can be used up to 30% in the diets of male coturnix.Keywords: Growth performance, Corn-DDGS, Male coturnix)